Y-Shaped Bilateral Self-Expandable Metallic Stent Placement for Malignant Hilar Biliary Obstruction: Data from a Referral Center for Palliative Care - R. Di Mitri; F. Mocciaro (The Scientific World Journal)
Background and Aim. Malignant hilar strictures are a clinical challenge because of the current therapeutic approach and the poor prognosis. In recent years, self-expandable metallic stents have proven more effective than plastic stents for palliation of malignant hilar strictures, with the bilateral stent-in-stent technique registering a high success rate. We report our experience with Y-shaped endoscopic self-expandable metallic stents placement for treatment of advanced malignant hilar strictures. Methods. From April 2009 to August 2012, we prospectively collected data on patients treated with Y-shaped SEMS placement for advanced malignant hilar carcinoma. Data on technical success, clinical success, and complications were collected. Results. Twenty patients (9 males) were treated (mean age 64.2 ± 15.3 years). The grade of malignant hilar strictures according to the Bismuth classification was II in 5 patients (25%), IIIa in 1 (5%), and IV in 14 (70%). The mean bilirubin level was 14.7 ± 4.9 mg/dL. Technical success was achieved in all patients, with a significant reduction in bilirubin levels (2.9 ± 1.7 mg/dL). One patient experienced cholangitis as early complication, while in 2 patients stent ingrowth was observed. No stents migration was recorded. There was no procedure-related mortality. At the end of the follow-up (7.1 ± 3.1 months), 13 of the 20 patients (65%) had died. Conclusions. Our experience confirms endoscopic bilateral self-expandable metallic stents placement with stent-in-stent technique (Y-shaped configuration) as a feasible, effective, and safe procedure for palliation of unresectable malignant hilar strictures.